ANALISIS BUSINESS PROCESS REENGINEERING UNTUK MENGEVALUASI, MEREKAYASA ULANG, DAN MEMPERBAIKI MONITORING KONTRAK PADA PT PLN (PERSERO) DIST. JATIM AREA MALANG. - Ni Luh Wisayani (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
The purpose of this study was to determine the procedures of monitoring contract business process ongoing at PT PLN (Persero) East Java Distribution Malang Area, to identify the causes of monitoring contract business processes less efficient, and the proposed draft Monitoring Contract business processes based on analysis of Business Process Reengineering (BPR) method. There are many contract between PT PLN with the vendor requires efficient business processes so that the contract can be completed on time. Nowadays business process monitoring contract is less efficient because many processes are still done manually and repeatedly. By using the BPR method, the authors could find out the cause of the lack of efficiency in the monitoring contract business process. The results of this research are the design recommendations of new monitoring contract business process with the proposed solution, there are uses integrated Monitoring System Contract between divisions, streamlining the process with disappearing NVA processes and simplification of the process time for BVA. The design of the new process can show time savings in monitoring contract business process as much as 31.39% - 44.51%. Keywords: Business Process, Monitoring Contract, BPR.Abstract The purpose of this study was to determine the procedures of monitoring contract business process ongoing at PT PLN (Persero) East Java Distribution Malang Area, to identify the causes of monitoring contract business processes less efficient, and the proposed draft Monitoring Contract business processes based on analysis of Business Process Reengineering (BPR) method. There are many contract between PT PLN with the vendor requires efficient business processes so that the contract can be completed on time. Nowadays business process monitoring contract is less efficient because many processes are still done manually and repeatedly. By using the BPR method, the authors could find out the cause of the lack of efficiency in the monitoring contract business process. The results of this research are the design recommendations of new monitoring contract business process with the proposed solution, there are uses integrated Monitoring System Contract between divisions, streamlining the process with disappearing NVA processes and simplification of the process time for BVA. The design of the new process can show time savings in monitoring contract business process as much as 31.39% - 44.51%. Keywords: Business Process, Monitoring Contract, BPR.